Thresholds for carcinogens. (25th May 2021) - Calabrese, Edward J.; Priest, Nicholas D.; Kozumbo, Walter J.
Abstract: Current regulatory cancer risk assessment principles and practices assume a linear dose-response relationship—the linear no-threshold (LNT) model—that theoretically estimates cancer risks occurring following low doses of carcinogens by linearly extrapolating downward from experimentally determined risks at high doses. The two-year rodent bioassays serve as experimental vehicles to determine the high-dose cancer risks in animals and then to predict, by extrapolation, the number of carcinogen-induced tumors (tumor incidence) that will arise during the lifespans of humans who are exposed to environmental carcinogens at doses typically orders of magnitude below those applied in the rodent assays. An integrated toxicological analysis is conducted herein to reconsider an alternative and once-promising approach, tumor latency, for estimating carcinogen-induced cancer risks at low doses. Tumor latency measures time-to-tumor following exposure to a carcinogen, instead of tumor incidence. Evidence for and against the concept of carcinogen-induced tumor latency is presented, discussed, and then examined with respect to its relationship to dose, dose rates, and the dose-related concepts of initiation, tumor promotion, tumor regression, tumor incidence, and hormesis. Considerable experimental evidence indicates: (1) tumor latency (time-to-tumor) is inversely related to the dose of carcinogens and (2) lower doses of carcinogens display quantifiably discrete latency thresholds below which the promotion and, consequently, the progression and growth of tumors are delayed or prevented during a normal lifespan. Besides reconciling well with the concept of tumor promotion, such latency thresholds also reconcile favorably with the existence of thresholds for tumor incidence, the stochastic processes of tumor initiation, and the compensatory repair mechanisms of hormesis. Most importantly, this analysis and the arguments presented herein provide sound theoretical, experimental, and mechanistic rationales for rethinking the foundational premises of low-dose linearity and updating the current practices of cancer risk assessment to include the concept of carcinogen thresholds. Highlights: Tumor latency is often inversely related to dose. Inverse dose latency concept can create thresholds for carcinogens. Cancer risk assessment should incorporate this dose latency concept.